Work to live or live to work? Unemployment, happiness, and culture - Annabelle Krause (Institute for the Study of Labor (IZA), 2011)
Happiness drops when individuals become unemployed. The negative impact of the unemployment shock, however, may differ by cultural background. To test the hypothesis of a 'Teutonic work ethic', this paper takes advantage of Switzerland in its cultural diversity. By comparing different cultural groups in the same institutional setting, I empirically test whether such deep psychological traits have an influence on how unemployment is perceived. It is found that unemployment has a significantly negative effect on life satisfaction in Switzerland. I furthermore present evidence which confirms to some extent the hypothesis that Swiss German individuals suffer more from unemployment, although for the most part, these results are without statistical significance. Swiss Germans are additionally found to be happier than their French-speaking compatriots' independent of whether they are unemployed. This difference between Romanic and Germanic cultural backgrounds is in line with previous findings, but deserves further research attention.
urn:nbn:de:101:1-201111213399
Keywords: J28; J60; Z1; 330; life satisfaction; unemployment; cultural differences; Switzerland; Arbeitslosigkeit; Zufriedenheit; Kulturelle Identität; Vergleich; Schweiz